Macroeconomic shocks across Central European Countries - Maria Piotrowska (European Regional Science Association (ERSA), 2001)
The purpose of the research was to investigate the transmission mechanism of macroeconomic shocks across EU countries and CECs. It was expected that the findings would allow to verify the following hypotheses.If it turns out that macroeconomic shocks can be transmitted from the EU to Central European countries (CECs) rather than in opposite way,one should not be afraid that asymmetric shocks across CECs will destabilise the European integration. Moreover,if the size of shocks to EU countries is much smaller than to CECs, this would suggest that the integration process creates mechanisms which limit the extent of the disturbances in output.Therefore, the access of CECs to EU is likely to accelerate reducing the size of shocks.The research was based on VAR models,to which Granger non-causality tests, deletion tests, variance decompositions were applied.
Keywords: 330